Observations on the Rearing of the Fish Siganus Guttatus ( Bloch) (Siganidae) in Brackfish Water Ponds in Southern Negros, Philippines - Luchavez, Julieta (Silliman Journal, 2024)
A growth rate study was conducted on Siganus guttatus fry in two brackish water ponds from 29 November 1979 to 20 September 1980. A total of. 342 acclimatized fish (3 batches) were released in Pond I and 190 in Pond II. In Pond I, the monthly increase was 7.46 g for the first batch, 5.58 g for the second batch and 6.20 g for the third batch. The fish in Pond II had the highest monthly increase of 13.58 g. Tolerance of this species to salinity, temperature and dissolved oxygen is discussed.